Implementation of the Dandan Omah Program in Realizing Livable Homes in Kedung Cowek Urban Village Surabaya City - Ghea Arnanda; Agus Widiyarta (Jurnal Kebijakan Publik, 2025)
The Dandan Omah program is a government initiative aimed at rehabilitating uninhabitable housing to assist low-income families in obtaining decent living conditions. This initiative is in accordance with Surabaya Mayor Regulation Number 7 of 2024 concerning the Social Rehabilitation of Uninhabitable Houses in Surabaya City. The purpose of this study is to analyze and describe the extent of the implementation of the Dandan Omah Program in Kedung Cowek Village, Surabaya City. The research method used is qualitative with a case study approach with the technique of determining informants through purposive sampling. The data collection technique was a combination of three ways, observation, interviews, and documentation. Data were collected through a triangulation of methods, including observation, interviews, and documentation, and were analyzed using the interactive model of analysis proposed by Miles, Huberman, and Saldana. The findings of this study focus on three focuses: (1) Program suitability with the target group: the program has clear objectives,policies, and budgeting that address the needs of the intended beneficiaries, supported by the e-Rutilahu coordination strategy; (2) Program suitability with the implementing organization: the implementers carry out their roles and responsibilities effectively, conduct outreach and training, and receive positive feedback from the program beneficiaries; (3) Suitability of the target group with the implementing organization: he program is well-targeted, appropriately implemented, and prioritizes poor families residing in uninhabitable housing. Nevertheless, the study also identifies an existing information gap between program implementers and beneficiaries, particularly regarding policy details and budget allocations.